Effects of oxidative modification on textural properties and gel structure of pork myofibrillar proteins. (July 2019) - Xia, Minquan; Chen, Yinxia; Guo, Juanjuan; Feng, Xiaolong; Yin, Xiaoli; Wang, Lan; Wu, Wenjin; Li, Zhenshun; Sun, Weiqing; Ma, Jing
Abstract: Isolated myofibrillar protein (MP) was treated by the oxidation system of FeCl3 (0.01 mM) at four different H2 O2 concentrations (0, 1, 10, 20 mM). The oxidation degree was determined by measuring the carbonyl and total sulphydryl values. The structure and physicochemical properties of MP gels were investigated by water holding capacity (WHC) evaluation, sodium dodecyl sulfate-polyacryl amide gel electrophoresis (SDS-PAGE), texture profile analysis (TPA), Raman spectroscopy, and NMR transverse relaxation (T2 ). The results of carbonyls and total sulphydryls indicated that oxidation degree of MP increased with increasing H2 O2 concentration. TPA showed that moderate oxidation (10 mM H2 O2 ) could improve the hardness, springiness, gumminess and cohesiveness of MP gels, but not contribute to the maintenance of their WHC, probably due to severe depolymerization of MPs, unfolding of α-helix, exposure of the hydrophobic groups and the migration of protein-associated water (T2b ) and intra-myofibrillar water (T21 ) to the longer relaxation time. Graphical abstract: Unlabelled Image Highlights: Oxidation affects the myofibrillar protein gel textural property and structure. Moderate oxidation (10 mM H2 O2 ) can improve the gel textural property. Gel water-holding capacity cannot be well maintained when oxidized at 1–20 mM H2 O2. α-helix, hydrophobic group and water changes decrease gel water-holding capacity.